Lineamientos para la elaboración de las principales políticas contables en las empresas camaroneras. - Ramon Vega, Andrea Viviana (My University, 2021)
The application of the International Financial Reporting Standards (IFRS) in the various companies is relevant since they are essential for the disclosure of economic transactions in the financial statements since this research is therefore focused on an analysis of accounting policies based on of accounting regulations International Accounting Standard 1 Presentation of Financial Statements and International Accounting Standard 8 Accounting Policies, Changes in Accounting Estimates and Errors in order to design a guideline of the main accounting policies as a tool for the preparation and presentation of financial reports in shrimp production companies. To achieve the purpose, the hermeneutical method will be executed, which is a quantitative approach, in addition to the bibliographic review that was taken as a reference for scientific articles, books. Additionally, a sketch will be made where the guidelines of the main accounting policies directed to companies that are dedicated to shrimp production will be demonstrated, resulting in the preparation and presentation of them in financial reports are necessary and their application is essential. Since, due to the requirements of the accounting regulations, the entities will be able to show reasonable information in the financial statements, and make a faithful and transparent presentation.
La aplicación de las Normas Internacionales de Información Financiera (NIIF) en las diversas empresas es relevante ya que son primordial para la revelación de las transacciones económicas en los estados financieros puesto que por ello la presente investigación se enfoca en un análisis de políticas contables a base de la normativa contable Norma Internacional de Contabilidad 1 Presentación de Estados Financieros y Norma Internacional de Contabilidad 8 Políticas Contables, Cambios en las Estimaciones Contables y Errores para con ello diseñar una guía de lineamientos de las principales políticas contables como herramienta para la elaboración y presentación de informes financieros en las empresas de producción camaronera. Para alcanzar el propósito se ejecutará el método hermenéutico el cual es de un enfoque cuantitativo, además de la revisión bibliográfica que se tomó como referencia de artículos científicos, libros. Adicionalmente se realizará un bosquejo donde se demostrara los lineamientos de las principales políticas contables direccionado a las empresas que se dedican a la producción de camarón, dando como resultado que la elaboración y presentación de las mismas en los informes financieros son necesarios y su aplicación es indispensable ya que a razón de los requerimientos de la normativa contable las entidades podrán evidenciar en los estados financieros una información razonable, y realizar una presentación fiel y transparente.
Keywords: POLÍTICAS CONTABLES; ESTADOS FINANCIEROS; NORMAS INTERNACIONALES DE CONTABILIDAD